Pendekatan Interdisipliner Terhadap Perilaku Konsumen Bank Syariah - Syaifuddin, Syaifuddin (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
Interdisciplinary is a collaboration between several disciplines to respond to developments and problems of human civilization. Mu'amalah science, economics, sociology, and psychology work together to examine the behavior of Muslim consumers. Consumer behavior is the study of how individuals, groups and organizations select, purchase, use and dispose of goods, services, ideas or experiences to satisfy their wants and needs. Consumer behavior studies focused on how individuals make the decision to utilize their resources (time, money and effort) to buy goods and services consumed. This interdisciplinary approach to the Islamic bank consumer behavior is required, because basically Islamic economics as a subject of study is the contribution of the various sciences. In a study of consumer behavior resulted in two conclusions Islamic bank. Religiosity influences customer behavior Islamic bank, and other conclusions stated that in a certain level of religiosity does not affect the behavior of bank customers Shari'ah.